REFLEKSI DAN DEKONSTRUKSI TEORI OPOSISI BINER DALAM TRADISI HINDU MASYARAKAT BALI - Sandiyasa, I Ketut (PANGKAJA: JURNAL AGAMA HINDU, 2018)
The background of this paper is to see the reflection and deconstruction of binary opposition theory in socio-religious Balinese society, considering the Balinese is known as a religious, aesthetic, and creative. Aim of this paper is to see the application of critical theories such as binary opposition theory, the decontruction of binary opposition in society, especially the people of Bali. In the reli- gious terminology, the binary opposition is called rwa bhineda, sekala-niskala, purusa-pradana, and linga-yoni. The Balinese acknowledged the contradictory opposition but did not denial. But the Balinese deconstruct the opposition with the same degree of recognition and for the realization of harmony. This unification is reflected in various Hindu traditions such as Usabha Kaulu and Daa Malom dance in Ngis village. Such reflection and decontruction prove the Balinese with local action and global thinking.